Criminal law measures to respond to an offense under Art. 231 k.k. made by a notary (Discourse of Law and Administration, 2023)
This publication presents the possible criminal law consequences of committing a crime by a notary under Article 231 of the Polish Penal Code. An analysis of the dimension of penalties was made, taking into account not only the sanction indicated in this provision, but also the regulations of the general part of the Penal Code. Possibilities of waiving the imposition of a penalty and applying the conditional discontinuance of proceedings are presented. The paper also discusses the dimension of punishment when a notary has committed a continuous crime under Article 12 § 1 of the Penal Code. The author also presents selected penal measures that may be imposed against a notary in the event of committing an offense under Article 231 of the Penal Code.
Keywords: criminal liability of notaries; prohibition from practicing notary profession; continuous act